Comparative Analysis of Various Irrigation Solutions in Root Canal Treatment - Mubashir Baig Mirza; Kirti Sharma; Chitharanjan Shetty; Jayantika Gupta; Kinjal Padariya; Hitesh Chohan; Alen Pius (Wolters Kluwer Medknow Publications, 2024)
Background: "Root canal treatment (RCT)" is essential in preserving natural dentition by eliminating infection within the root canal system. Irrigation solutions play a crucial role in achieving successful RCT outcomes by facilitating disinfection and debris removal. Methods: An in vitro experimental design was employed to evaluate the irrigation solutions. Antimicrobial efficacy was assessed using agar diffusion assays against Enterococcus faecalis and Candida albicans. Tissue dissolution ability was evaluated by measuring the weight loss of dentin specimens. Cytotoxicity was assessed using cell viability assays with human periodontal ligament fibroblasts. Results: NaOCl demonstrated the highest antimicrobial efficacy, while EDTA exhibited superior tissue dissolution ability. CHX and QMix displayed lower cytotoxicity compared to NaOCl and EDTA. Conclusion: The choice of irrigation solution in RCT should consider factors such as antimicrobial efficacy, tissue dissolution ability, and cytotoxicity. NaOCl remains effective but has high cytotoxicity, whereas CHX and QMix offer alternatives with lower cytotoxicity. EDTA is effective in tissue dissolution but should be used cautiously due to cytotoxic potential. Clinicians should weigh the benefits and limitations of each solution for optimal treatment outcomes.